Maternal depression and co‐occurring antisocial behaviour: testing maternal hostility and warmth as mediators of risk for offspring psychopathology. (27th June 2013) - Sellers, Ruth; Harold, Gordon T.; Elam, Kit; Rhoades, Kimberly A.; Potter, Robert; Mars, Becky; Craddock, Nick; Thapar, Anita; Collishaw, Stephan
<x xml:space="preserve">Abstract</x> Background Disruption in the parent–child relationship is a commonly hypothesized risk factor through which maternal depression may increase risk for offspring psychopathology. However, maternal depression is commonly accompanied by other psychopathology, including antisocial behaviour. Few studies have examined the role of co‐occurring psychopathology in depressed mothers. Using a longitudinal study of offspring of mothers with recurrent depression, we aimed to test whether maternal warmth/hostility mediated links between maternal depression severity and child outcomes, and how far direct and indirect pathways were robust to controls for co‐occurring maternal antisocial behaviour. Methods Mothers with a history of recurrent major depressive disorder and their adolescent offspring (9–17 years at baseline) were assessed three times between 2007 and 2010. Mothers completed questionnaires assessing their own depression severity and antisocial behaviour at Time 1 (T1). The parent–child relationship was assessed using parent‐rated questionnaire and interviewer‐rated 5‐min speech sample at Time 2 (T2). Offspring symptoms of depression and disruptive behaviours were assessed using the Child and Adolescent Psychiatric Assessment at Time 3 (T3). Results Maternal hostility and warmth, respectively, mediated the association between maternal depression severity and risk for offspring psychopathology. However, the effects were attenuated when maternal antisocial behaviour was included in the analysis. In tests of the full theoretical model, maternal antisocial behaviour predicted both maternal hostility and low warmth, maternal hostility predicted offspring disruptive behaviour disorder symptoms, but not depression, and maternal warmth was not associated with either child outcome. Conclusions Parenting interventions aimed at reducing hostility may be beneficial for preventing or reducing adolescent disruptive behaviours in offspring of depressed mothers, especially when depressed mothers report co‐occurring antisocial behaviour.